Adjunctive esketamine in propofol-based sedation for gastrointestinal endoscopy: a systematic review and meta-analysis of randomized trials - Qi, Jiazheng; Luo, Mengqiang; Zong, Wenru; Zhang, Lingjing; Chen, Baoxuan; Yang, Xiaoyu; Xu, Bo; Zhao, Xu (Frontiers in Pharmacology, 2025)
BackgroundWhile propofol is widely used for gastrointestinal endoscopic sedation, its cardiovascular and respiratory side effects and lack of analgesia can compromise safety and comfort. Esketamine provides both sedation and analgesia with minimal hemodynamic or respiratory impact. Combining esketamine with propofol may miti-gate propofol’s adverse effects while enhancing sedation quality. However, the com-bination’s overall safety and efficacy remain inconclusive.MethodsThis systematic review and meta-analysis compared propofol-based sedation with versus without intravenous esketamine in gastrointestinal endoscopy, synthesizing evidence from randomized controlled trials. The primary outcome was the incidence of hypotension. Secondary outcomes included intraoperative adverse respiratory events, propofol consumption, involuntary movement, hypertension, arrhythmias, PONV recovery times, and dizziness.ResultsEighteen trials were included in the analysis. Additional esketamine significantly reduced the incidence of hypotension (risk ratio [RR]: 0.32; 95% confidence interval [CI]: 0.24 to 0.43; P < 0.01; I2 = 44.4%; moderate quality). The addition of esketamine to propofol can reduce the incidence of adverse respiratory events (RR: 0.57, 95% CI: 0.38 to 0.86; P < 0.01; I2 = 67.8%; moderate quality). Esketamine added to propofol decreased involuntary movement (RR: 0.61, 95% CI: 0.42 to 0.92; P = 0.02; I2 = 77.2%; low quality) and reduced the propofol consumption (mean difference [MD]: −0.94, 95% CI: −1.53 to −0.35 mg/kg; P < 0.01; I2 = 96.2%; low quality). No significant differences were found for hypertension, arrhythmias, PONV, recovery time or dizziness.ConclusionSupplementing propofol-based sedation with esketamine reduced the risk of hypotension and adverse respiratory events, without increasing cardiovascular complications, or extending recovery-time.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD420251030940.